English Pre-Service Teachers’ Self-Assessment of Their Classroom-Based Assessment Practices - Hanifah Suci Rachmawati; Joko Priyana (International Journal of Contemporary Studies in Education (IJ-CSE), 2026)
Purpose – Pre-service teachers still face considerable challenges in Classroom-Based Assessment (CBA) practices. In addition, far too little attention has been paid to the pre-service teachers' self-assessment of their CBA practices especially those attending the Pre-Service Teacher Professional Education program. This study set out to investigate the English pre-service teachers’ self-assessment of their CBA practices. It investigates their skill level in enacting each stage of CBA. Methodology – This study is an explanatory sequential mixed-method research. Thus, the quantitative and qualitative method were used in a single study. Eighty-four English pre-service teachers participated in filling out the questionnaire then an interview was conducted as the follow-up. Findings – The initial result to emerge from the questionnaire was that the English pre-service teachers assessed themselves competent in planning, monitoring, recording and disseminating the assessment. Additionally, most of them were proficient in implementing the assessment. However, none of them perceived that they were expert in enacting all the CBA stages though they already possessed the theoretical knowledge and practical experience during the Pre-Service Teacher Professional Education (PPG Prajabatan) program. Novelty – This study showed that English pre-service teachers were in the view that self-assessment assisted them to recognize their strengths, weaknesses, and determine the areas that needed improvement. Likewise, self-assessment also served as a means for professional growth. Significance – English pre-service teachers especially those taking Pre-Service Teacher Professional Education can use the results of the study to reflect on their Classroom-Based Assessment (CBA) practices, recognize their strengths and weaknesses, and enhance their practices and as a guideline to self-assess their practices.